A simulation framework for studying blocking effects in warehouse systems with autonomous vehicles. (2016) - Roy, Debjit; Krishnamurthy, Ananth; Heragu, Sunderesh S.; Malmborg, Charles J.
Autonomous vehicles-based storage and retrieval systems (AVS/RS) have been shown to offer greater flexibility to improve cycle time and throughput capacity in the transfer of unit loads in high-density storage areas of warehouses. In these systems, loads are transferred by autonomous vehicles that move horizontally along aisles and cross-aisles within a tier, while lifts support vertical movement of loads between tiers. For analytical tractability, prior studies on performance evaluation of AVS/RS have ignored the blocking effects of vehicles and lifts while estimating throughput capacity and cycle times. To evaluate the effects of blocking on system performance, this paper first develops protocols to address vehicle blocking that are subsequently incorporated in a detailed simulation model. The blocking effects are studied for a variety of tier configurations that differ in depth/width ratio, number of locations, number of available vehicles, and transaction arrival rates. Results suggest that blocking delays could account for 2%-20% of the transaction cycle times. [Received 17 October 2013; Revised 28 August 2014; Revised 23 December 2014; Accepted 2 April 2015]